2015
DOI: 10.1055/s-0034-1395615
|View full text |Cite
|
Sign up to set email alerts
|

The VGF-Derived Neuropeptide TLQP-21 Shows No Impact on Hormone Secretion in the Isolated Perfused Rat Pancreas

Abstract: TLQP-21 is a VGF-derived neuropeptide proposed to be involved in regulation of metabolism. More specifically it has been suggested that TLQP-21 has the ability to enhance glucose stimulated insulin secretion, making it a candidate for treatment of patients with type 2 diabetes.In this study, we investigated the impact of TLQP-21 on insulin, glucagon, and somatostatin secretion in the perfused rat pancreas. We found that administration of 5 and 50 nM TLQP-21 had no impact on pancreatic hormone secretion at 3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…We used the physiologically relevant isolated perfused rat pancreas model [7] and found that SGLT2 activity had no effect on glucagon secretion whether transporter activity was inhibited by dapagliflozin or phloridzin or whether it was activated by the SGLT-specific substrate α-MGP. Of note, the dapagliflozin concentration used (0.5 μmol/l) matches peak plasma concentration in humans after intake of therapeutic doses (5-10 mg/day) [24] and, in all experiments, secretion was tightly regulated by the glucose concentration so glucagon secretion was high at low glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the physiologically relevant isolated perfused rat pancreas model [7] and found that SGLT2 activity had no effect on glucagon secretion whether transporter activity was inhibited by dapagliflozin or phloridzin or whether it was activated by the SGLT-specific substrate α-MGP. Of note, the dapagliflozin concentration used (0.5 μmol/l) matches peak plasma concentration in humans after intake of therapeutic doses (5-10 mg/day) [24] and, in all experiments, secretion was tightly regulated by the glucose concentration so glucagon secretion was high at low glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aim of this study was to test whether the effects of SGLT2 on glucagon secretion demonstrated in vitro could be reproduced in a more physiological setting. As glucagon secretion is tightly regulated by blood glucose, which is lowered by SGLT2 inhibitors, we chose the isolated perfused rat pancreas as experimental model [6,7], where perfusate glucose is kept constant. We studied the effects of the SLGT2 inhibitor dapagliflozin, the SGLT1/2 inhibitor phloridzin and the metabolically inert SGLT-specific substrate methyl-α-D-glucopyranoside (α-MGP) on glucagon secretion in this model.…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid appears to behave similarly to linoleic acid in its ability to induce GLP‐1 release from the vascular, but not from the luminal side. Linoleic acid is an essential fatty acid, introduced with the diet and capable of stimulating GLP‐1 release from the isolated rat small intestine from the vascular side only . Nevertheless, it should also be noted that ABA administration in the intestinal perfusion system gave similar results to taurodeoxycholate (TDCA).…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid is an essential fatty acid, introduced with the diet and capable of stimulating GLP-1 release from the isolated rat small intestine from the vascular side only. 28 Nevertheless, it should also be noted that ABA administration in the intestinal perfusion system gave similar results to taurodeoxycholate (TDCA). Application of 100 μmol/L TDCA, via the vasculature, in perfused rat small intestine, robustly increased GLP-1 release, whereas luminal application of TDCA at the same concentration was significantly less effective, 29 presumably because TDCA stimulates GLP-1 secretion by postabsorptive activation of basolateral located Taconic-G-proteincoupled receptors (TGR5).…”
Section: Aba Stimulates Glp-1 Secretion From the Proximal Small Intmentioning
confidence: 92%
“…Indeed, chronic icv administration of the VGF-derived peptide TLQP-21 increased energy expenditure and body temperature and limited diet-induced obesity in mice (Bartolomucci et al, 2006), and decreased food intake, body weight and adiposity in Siberian hamsters (Jethwa et al., 2007). Peripheral ip administration of TLQP-21 increased lipolysis (Possenti et al, 2012), and enhanced glucose-stimulated insulin secretion in human and rat islets and improved glycemic control in vivo (Stephens et al, 2012), but had no effect on hormone secretion in perfused rat pancreas (Christiansen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%